PENGAJUAN GUGATAN PEMBATALAN PERKAWINAN OLEH PEGAWAI PENCATAT NIKAH DITINJAU DARI PERSPEKTIF HUKUM POSITIF DAN MAQASHID SYARI’AH - Zainal Arifin Purba & Fatimah (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2022)
True marriage is to connect the bond between a man and a woman in forming a happy and eternal household based on the One Godhead. However, the marriage institution that has been built can still be canceled due to the discovery of legal defects in the future. The annulment of this marriage is annulled by positive law in Indonesia as well as in fiqh, in this case the provisions of Islamic law that live and develop in Indonesia.